STUDI KOMPARASI KEMAMPUAN MEMBACA AL-QUR’AN BERDASARKAN LATARBELAKANG P ENDIDIKAN SISWA KELAS VIII DI SMP NEGERI 40 PALEMBANG - Amelia Agustina; Muhammad Isnaini; Nyayu Soraya (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2021)
In State Junior High School 40 Palembang, they have different educational backgrounds. Consists of students graduating from Islamic High Boarding School (MI) and students graduating from Elementary School (SD). In schools, especially in the subject of Islamic Religious Education between Elementary School and Islamic High Boarding School there are differences. namely the allocation of time and religious material. The existence of different educational backgrounds will certainly provide different support and obstacles.Researcher wanted to compare the reading ability of the Al-Qur'an of Islamic High Boarding School and Elementary School graduate students with the title